2019
DOI: 10.4103/jfmpc.jfmpc_142_19
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic precision of apparent diffusion coefficient (ADC) in grading of malignant endometrial lesions compared with histopathological findings

Abstract: Objective:The present study aimed to extract apparent diffusion coefficient (ADC) values from the diffusion-weighted imaging (DWI) sequence of endometrial lesions and compare them with tissue specimen results in order to determine the precision of ADC values in grading of malignant endometrial lesions.Methods:The present prospective study was conducted on 22 patients complaining of abnormal vaginal bleeding or evidence for endometrial thickening or masses detected using the ultrasound. Sampling was performed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Presented findings indicated that DWI (93.3 %) was more sensitive than T2WI (86.7 %) and DCE (89.6 %) in distinguishing benign from malignant lesions. This was the same conclusion of study by Gharibvand et al 13 and Masroor et al, 14 the latter of whom reported that DWI is more sensitive to small lesions than T2. Compared to T2WI (91.4 %) and DWI (94.8 %), DCE had the highest specificity (98.4 %).…”
Section: Discussionsupporting
confidence: 88%
“…Presented findings indicated that DWI (93.3 %) was more sensitive than T2WI (86.7 %) and DCE (89.6 %) in distinguishing benign from malignant lesions. This was the same conclusion of study by Gharibvand et al 13 and Masroor et al, 14 the latter of whom reported that DWI is more sensitive to small lesions than T2. Compared to T2WI (91.4 %) and DWI (94.8 %), DCE had the highest specificity (98.4 %).…”
Section: Discussionsupporting
confidence: 88%
“…In the current study, benign lesions were present in 68.9% of female patients, with endometrial polyp and simple endometrial hyperplasia being the most common, as in the study of Elsammak et al and Gharibvand et al (17,21). Literature data point to a risk of progression of endometrial hyperplasia to EC up to 5% for endometrial hyperplasia without cell atypia and even 30% in the case of hyperplasia with atypia (30).…”
Section: Discussionsupporting
confidence: 76%
“…In previous research the most attention has been devoted to examining the role of DWI and ADC in the differentiation of EC from various benign endometrial lesions in a more precise diagnosis of EC, as well as to the possibility of determining its histological grade (10,(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…The apparent diffusion coefficient (ADC) of diffusion-weighted imaging (DWI) can reflect the malignancy of the tumor, which has been proved to be valuable in the diagnosis, typing and grade of EC [ 10 – 12 ]. Gharibvand et al [ 11 ]. reported that DWI sequence (ADC value) had high accuracy in diagnosing benign endometrial lesions and differentiating malignant lesions.…”
Section: Introductionmentioning
confidence: 99%